Corporate Financial Dynamics Under The Shadow of Financial Distress and Tax Avoidance Strategies - Dewi Sarifah Tullah; Kusuma Dewi; Elis Mediawati; Farah Akmar Anor Salim; Jan Febrian (Universitas Swadaya Gunung Jati, 2025)
An efficient and equitable tax system is vital for fostering national economic growth. However, tax avoidance remains a major challenge, particularly in the infrastructure sector which holds strategic importance. This study aims to examine the effect of thin capitalization, rentability, and operating cash flow on tax avoidance, with financial distress as a mediating variable. Using a quantitative approach with secondary data from the financial statements of 220 infrastructure firms listed on the IDX during 2019–2023, the analysis employed multiple linear regression and the Sobel test. The results indicate that all three independent variables significantly influence both financial distress and tax avoidance, directly and indirectly. Thin capitalization and operating cash flow increase tax avoidance incentives, while financial distress reduces such tendencies. These findings support agency, trade-off, and signaling theories. The study's implications highlight the need for balanced tax policy oversight and corporate financial management, especially under financial pressure. Theoretical contributions include the use of the book-tax difference proxy, while practical insights are intended for policymakers and corporate managers to formulate fair and sustainable tax strategies.